Republic of Armenia : Sixth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility -Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Republic of Armenia. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
Macroeconomic performance of Armenia in 2007 has been strong, with double-digit growth and single-digit inflation for the sixth consecutive year. Fiscal policy in 2007 remains prudent, with the central government deficit limited to the programmed level of 1.8 percent of GDP. Monetary growth has accelerated in 2007, fueled by unsterilized foreign exchange intervention, cash dedollarization, and a surge in private sector credit. External developments in 2007 have shaped by large-scale inflows, high food prices, and buoyant domestic demand, amid continued dram appreciation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet